Modulation of brain glutamate dehydrogenase as a tool for controlling seizures - Rasgado Lourdes A. Vega; Reyes Guillermo Ceballos; Díaz Fernando Vega (Acta Pharmaceutica)
Glutamate (Glu) is a major excitatory neurotransmitter involved in epilepsy. Glu is synthesized by glutamate dehydrogenase (GDH, E.C. 1.4.1.3) and dysfunction of the enzymatic activity of GDH is associated with brain pathologies. The main goal of this work is to establish the role of GDH in the effects of antiepileptic drugs (AEDs) such as valproate (VALP), diazepam (DIAZ) and diphenylhydantoin (DPH) and its repercussions on oxygen consumption. Oxidative deamination of Glu and reductive amination of aketoglutarate (αK) in mice brain were investigated. Our results show that AEDs decrease GDH activity and oxygen consumption in vitro. In ex vivo experiments, AEDs increased GDH activity but decreased oxygen consumption during Glu oxidative deamination. VALP and DPH reversed the increase in reductive amination of αK caused by the chemoconvulsant pentylenetetrazol. These results suggest that AEDs act by modulating brain GDH activity, which in turn decreased oxygen consumption. GDH represents an important regulation point of neuronal excitability, and modulation of its activity represents a potential target for metabolic treatment of epilepsy and for the development of new AEDs.